Tinjauan kriminologi terhadap Pelaku Kejahatan Pencurian Listrik di wilayah kota kendari : Studi Kasus PLN up3 kendari 2023-2024 - Hery Setiawan Ardi Syahputro; Arifai Arifai; Gamlan Dagani (JURNAL HUKUM PELITA, 2025)
This study discusses the factors that influence and constrain officers in preventing electricity theft in the PLN UP3 Kendari area. In this era, electricity has become a basic necessity for human life, resulting in electricity abuse by PLN customers. This study uses an empirical juridical research method that examines the laws that operate and are applied in society. The results of this study found that the factors causing electricity theft at PLN UP3 Kendari are insufficient electricity supply, electricity payments that are considered too expensive by customers, and the installation of illegal Kwh meters by the installation party. Meanwhile, the obstacles faced by officers in preventing electricity theft are customer resistance and officers who deny their actions, and requests for security from the police with the aim of making activities conducive and effective.